Intrauterine insemination—No more Mr. N.I.C.E. guy?. (March 2017) - Geisler, Minna E.; Ledwidge, Mark; Bermingham, Margaret; McAuliffe, Mary; McMenamin, Moya B.; Waterstone, John J.
Abstract: Objective: To determine the per cycle chance of a live birth and to identify factors that may support a more individualised application of IUI in view of National Institute for Health and Care Excellence (NICE) updated guideline on fertility 2013. Study design: A retrospective, cohort study of 851 couples (1688 cycles) with unexplained, mild endometriosis, one patent Fallopian tube (with ovulation occurring in the corresponding ovary), mild male factor or ovulatory dysfunction, who initiated their first cycle of IUI/COH during the study period 2009–2013 and completed up to 3 cycles. Exclusion criteria included donor sperm and diminished ovarian reserve. Success factors and probabilities were determined based on live birth rates. Results: Mean age was 33.8 ± 3.3 years and mean duration of subfertility was 2.28 ± 1.47 years. Independent associates of successful outcome factors were lower age (AOR 0.93; 95%CI 0.89–0.98, p = 0.007) and multiparity (AOR 1.72; 95%CI 1.17–2.52). Live-birth rates declined independently of other factors from 15.3% (n = 130/851) in cycle 1–7.0% (n = 19/273) in cycle 3 (AOR 0.76; 95%CI, 0.62–0.93, p = 0.008). Per cycle probabilities of live birth ranged from 21.4% to 5.1% dependent on age, cycle number and previous parity. The unadjusted cumulative pregnancy rate for live birth per cycle started, over three cycles, was 34.9% with a multiple live birth rate per cycle started of 5.4%. The associates of live birth amongst those with unexplained sub-fertility only (n = 632, first cycle attempt) were also analysed, yielding similar results. Conclusions: IUI/COH is a simple treatment that produces good live birth rates, especially in younger patients and/or those with previous parity. More than 90% of total live births with IUI/COH is achieved during the first two cycles. As a retrospective, observational study, there is no comparator group and therefore we cannot comment on the relative efficacy of up to three IUI cycles over expectant management in a similar cohort. Our study suggests that probabilities of success can be used to individualise treatment decisions and that there is merit in continuing to offer IUI before resorting to IVF for certain patients.